Effect of TRA-8 Anti-Death Receptor 5 Antibody in Combination With Chemotherapy in an Ex Vivo Human Ovarian Cancer Model. Issue 5 (1st July 2009) - Frederick, Peter J.; Kendrick, James E.; Straughn, J. Michael; Della Manna, Debbie L.; Oliver, Patsy G.; Lin, Hui-Yi; Grizzle, William E.; Stockard, Cecil R.; Alvarez, Ronald D.; Zhou, Tong; Lobuglio, Albert F.; Buchsbaum, Donald J.
Abstract : Objectives: To investigate the cytotoxicity of TRA-8, an antibody that specifically binds death receptor 5, alone and in combination with chemotherapy, using an ex vivo human ovarian cancer model. Materials and Methods: Twenty-six ovarian cancer specimens were obtained during ovarian cancer debulking, and tumor slices were prepared with the Krumdieck tissue slicer. The tumor slices were exposed to varying concentrations of TRA-8, carboplatin/paclitaxel, or the combination of TRA-8 and chemotherapy. Using nonlinear modeling, dose-response curves and IC50 values were generated for specimens treated with TRA-8. The additive and synergistic cytotoxic effects of chemotherapy combination with TRA-8 were evaluated in specimens. In addition to adenosine triphosphate viability assays, the treated and untreated slices were assessed by immunohistochemistry to confirm apoptosis induction. Results: Specimens from 13 patients yielded TRA-8-induced IC50 values. Of these specimens, 15% were found to be sensitive to TRA-8-induced cytotoxicity at IC50 doses less than 500 ng/mL. Specimens from 13 patients underwent combination treatment with TRA-8 and carboplatin/paclitaxel. Of these specimens, 77% exhibited additive cytotoxicity in comparison with those treated with either agent alone, whereas 15% exhibited synergistic cytotoxicity. Immunohistochemical analysis of terminal deoxynucleotidyl transferase biotin-dUTP nick end labeling and cleaved caspase 3 staining demonstrated a dose-dependent increase in apoptosis with the combination treatment. Conclusions: This study demonstrates the efficacy of the death receptor monoclonal antibody TRA-8 in combination with conventional chemotherapy in an ex vivo human ovarian cancer model. This model can be used to assess cytotoxicity of novel agents in combination with chemotherapy in ovarian cancer.